2011
DOI: 10.1038/ismej.2011.5
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic growth of nitrifying community in an agricultural soil

Abstract: The two-step nitrification process is an integral part of the global nitrogen cycle, and it is accomplished by distinctly different nitrifiers. By combining DNA-based stable isotope probing (SIP) and high-throughput pyrosequencing, we present the molecular evidence for autotrophic growth of ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA) and nitrite-oxidizing bacteria (NOB) in agricultural soil upon ammonium fertilization. Time-course incubation of SIP microcosms indicated that the amoA genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
192
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(224 citation statements)
references
References 59 publications
29
192
2
1
Order By: Relevance
“…The archaea have previously been widely found in soils (Sims et al, 2012;Taylor et al, 2012), and they can be distinguished from bacteria by their adaptation to chronic energy stress (Valentine, 2007), but their ecological roles are still not well known. The greater abundance of AOA (24.5 and 2.3 times more) than AOB in the rhizospheres of maize and faba bean is consistent with some previous reports in agricultural soils (Leininger et al, 2006;Sims et al, 2012), but differed from the result of Xia et al (2011) who reported that AOB were dominated for the nitrification process in an agricultural soil. Two factors, soil pH value and NH 4 + content, have been evidenced to be the determinants for the ratio of AOA:AOB.…”
Section: Discussionsupporting
confidence: 89%
“…The archaea have previously been widely found in soils (Sims et al, 2012;Taylor et al, 2012), and they can be distinguished from bacteria by their adaptation to chronic energy stress (Valentine, 2007), but their ecological roles are still not well known. The greater abundance of AOA (24.5 and 2.3 times more) than AOB in the rhizospheres of maize and faba bean is consistent with some previous reports in agricultural soils (Leininger et al, 2006;Sims et al, 2012), but differed from the result of Xia et al (2011) who reported that AOB were dominated for the nitrification process in an agricultural soil. Two factors, soil pH value and NH 4 + content, have been evidenced to be the determinants for the ratio of AOA:AOB.…”
Section: Discussionsupporting
confidence: 89%
“…acidic conditions, which could block the direct delivery of fresh ammonia substrates to ammonia oxidizers. A previous study found that autotrophic ammonia oxidation was dominated by AOA in a pH 7.5 grassland soil without the external nitrogen supply , and contrasting findings demonstrated that AOB rather than AOA controlled the nitrification in two agricultural soils with weekly nitrogen fertilization at pH 7.0 (Jia and Conrad, 2009) and 8.0 (Xia et al, 2011), respectively. These three DNA-SIP incubations have a similar soil pH range, but differ in the availability of ammonia substrate.…”
Section: Discussionmentioning
confidence: 83%
“…Because of the development of new technologies like DNA-stable isotope probing (SIP), we could now be able to gain a deep insight into the autotrophic nitrification activity in complex soil environments. 13 CO 2 -DNA-SIP has shown its powerful potential to directly link CO 2 -incorporating ammonia oxidizers with nitrification activity in several neutral or alkaline soils (Jia and Conrad, 2009;Zhang et al, 2010;Pratscher et al, 2011;Xia et al, 2011) and provided evidence for autotrophic growth of N. devanaterra in acidic soil, whereas to the best of our knowledge, no study has been able to clearly identify the dominating ammonia oxidizers in the autotrophic nitrification of acidic soils.…”
Section: Introductionmentioning
confidence: 98%
“…A case can be made that the relative contributions of AOA and AOB to soil nitrification might shift in different phases of crop rotation and during different seasons of the year. Although recent studies have evaluated AOA and AOB population sizes, composition and/or their relative growth responses in soils recovered from agricultural cropping systems, the soils were often taken from complex crop rotations in multi-year cycles, and sampled in either spring, fall or unspecified times (Tourna et al, 2008;Hallin et al, 2009;Wessen et al, 2010Wessen et al, , 2011Xia et al, 2011). Clearly, the extent to which phase of the crop rotation or time of soil sampling might have influenced the results cannot be determined.…”
Section: Introductionmentioning
confidence: 99%